Ijtihad sebagai Sarana Merajut Nilai Kemaslahatan dan Keadilan Umat - Roqib, Moh. (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Islam is prominent and actual in every occation, however problrms are always rising. To handle those problems, ijtihad or a process to obtain operational Islamic law is considered by some Moslem scholars as one solutions. Ijtihad which is relative and tentantive is used for gaining the shari’a’s aim (maqasid al-shari’a), society peaceful (maslahah ‘ammah).